2022
DOI: 10.3389/fonc.2022.903560
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of Surgical Resection for Pancreatic Neuroendocrine Tumors With Oligometastatic Liver Metastasis: A Retrospective and Propensity Score-Matching Analysis

Abstract: BackgroundPancreatic neuroendocrine tumors (PanNETs) are a heterogeneous group of pancreatic malignancies. Surgical resection is the only curative treatment option for patients with localized PanNETs, yet the role of cancer-directed surgery (CDS) in the setting of oligometastatic liver metastasis remains a controversy.MethodsAll patients diagnosed with PanNETs and liver-only metastasis from 2010 to 2018 were identified from the SEER database. The biases of baseline characteristics between CDS and no-CDS cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Unfortunately, only a few studies have demonstrated the potential survival benefit of CDS in patients with M1 HNC, 7,23 and there is a lack of relevant research identifying which patients may benefit most from CDS treatment. In recent years, several studies have supported the survival benefit of CDS in metastatic pancreatic cancer and metastatic breast cancer 24–27 . Although our study was a retrospective analysis, it demonstrated in a large propensity score‐matched patient cohort that CDS offered a survival benefit for M1 HNC.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Unfortunately, only a few studies have demonstrated the potential survival benefit of CDS in patients with M1 HNC, 7,23 and there is a lack of relevant research identifying which patients may benefit most from CDS treatment. In recent years, several studies have supported the survival benefit of CDS in metastatic pancreatic cancer and metastatic breast cancer 24–27 . Although our study was a retrospective analysis, it demonstrated in a large propensity score‐matched patient cohort that CDS offered a survival benefit for M1 HNC.…”
Section: Discussionmentioning
confidence: 62%
“…In recent years, several studies have supported the survival benefit of CDS in metastatic pancreatic cancer and metastatic breast cancer. [24][25][26][27] Although our study was a retrospective analysis, it demonstrated in a large propensity score-matched patient cohort that CDS offered a survival benefit for M1 HNC. More importantly, the subgroup analysis results can help clinicians to select patients who will most likely benefit from CDS treatment, which may also facilitate recruitment into randomized controlled trials.…”
Section: Discussionmentioning
confidence: 86%